MENGGALI ARTI, MAKNA, DAN HAKIKAT FILSAFAT ILMU: RELEVANSI EPISTEMOLOGI DALAM DINAMIKA PENGETAHUAN MODERN - Rahman, Zaky Dhiaulhaq; Sarmain, Sarmain; Faqih, Saad Al; Fauzizak, Anis; Hidayat, Wahyu (Jurnal Manajemen Pendidikan, 2024)
This research explores the meaning, meaning, and essence of the philosophy of science as well as the relevance of epistemology in the dynamics of modern knowledge. Philosophy of science plays a key role in shaping a critical, systematic, and rational scientific thinking framework. In the era of rapid development of science and technology, the philosophy of science serves as the basis for distinguishing legitimate scientific knowledge from pseudoscience. In addition, the philosophy of science helps direct the development of knowledge by emphasizing the importance of valid and reliable scientific methods. Epistemology, as a branch of the philosophy of science that studies theories of knowledge, also plays a key role in assessing the validity and reliability of information, especially in the digital age where misinformation and disinformation are often widespread. With a qualitative approach based on literature study, this study examines the role of philosophy of science in supporting the development of science and technology and the importance of the epistemological framework in keeping scientific integrity. The results of this study show that the philosophy of science not only serves as a theoretical foundation, but as a practical tool to face modern challenges in science, including artificial intelligence and big data.